METHODOLOGY FOR IMPROVING PHYSICAL ENDURANCE IN FIELD HOCKEY AMONG GIRLS AGED 10-12 (Scientific journal of the Fergana State University, 2026)
This article analyzes methodological approaches aimed at improving physical endurance in 10–12-year-old girls engaged in field hockey. The study explores the growing popularity of field hockey among youth, the physical characteristics of the sport, and types of movements that require endurance, all examined on a scientific basis. In addition, the article provides recommendations for developing an effective training system, taking into account the physiological characteristics of the growing body. The results of the study are of practical significance for coaches and specialists working with young athletes and contribute to the improvement of training processes in field hockey.